2003
DOI: 10.1046/j.1460-9568.2003.02547.x
|View full text |Cite
|
Sign up to set email alerts
|

D2 Dopamine receptor blockade results in sprouting of DA axons in the intact animal but prevents sprouting following nigral lesions

Abstract: Recently it was demonstrated that sprouting of dopaminergic neurons and a microglial and astrocyte response follows both partial lesions of the substantia nigra pars compacta and blockade of the D2 dopamine receptor. We therefore studied the effects of the combination of these two treatments (lesioning and D2 dopamine receptor blockade). Haloperidol administration caused a 57% increase in dopaminergic terminal tree size (measured as terminal density per substantia nigra pars compacta neuron) and an increase of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 60 publications
1
20
0
Order By: Relevance
“…These drugs also inhibited neuronal migration, and it is unclear to what extent the effects on axons were direct or reflected abnormal positioning. In rats, haloperidol reduced the density of dopaminergic axon terminals when administered immediately after a lesion to the substantia nigra, but improved dopamine terminal sprouting when administered after a delay (Tripanichkul et al, 2003), suggesting that the growth response of neurons to haloperidol can vary dramatically under slightly different circumstances. This parallels our observations that PhAPs can have either no effect or a robust growth-promoting effect when added to cells that are growing under permissive versus inhibitory conditions, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…These drugs also inhibited neuronal migration, and it is unclear to what extent the effects on axons were direct or reflected abnormal positioning. In rats, haloperidol reduced the density of dopaminergic axon terminals when administered immediately after a lesion to the substantia nigra, but improved dopamine terminal sprouting when administered after a delay (Tripanichkul et al, 2003), suggesting that the growth response of neurons to haloperidol can vary dramatically under slightly different circumstances. This parallels our observations that PhAPs can have either no effect or a robust growth-promoting effect when added to cells that are growing under permissive versus inhibitory conditions, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…, 2001, 2002) whereas pharmacological blockade or genetic deletion of the D2R induced an increase in the terminal arbour volume (Parish et al. , 2002; Tripanichkul et al. , 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo studies in rats and mice have shown that the chronic blockade of D2R regulates the size of the terminal arbor in DA neurons of the substantia nigra (Parish et al. , 2002; Tripanichkul et al. , 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In an opposite manner, pharmacological blockade or genetic deletion of the D2R induced an increase in the terminal arbor volume (Parish et al. , 2002; Tripanichkul et al. , 2003).…”
Section: Discussionmentioning
confidence: 99%